From Top-Down to Bottom-Up: How Participative Supervision Models Enhance Teacher Performance - Hanif, Mamun; Riyadi, Ridho; Fatwa, Alyan (JURNAL AL-TANZIM, 2025)
This study aims to analyze the implementation of the top-down supervision model in Madrasah Tsanawiyah and explore how shifting towards a participatory supervision model can enhance teacher performance. This study is based on the argument that the supervision paradigm needs to be changed to be more sensitive to the needs and aspirations of teachers, considering that teachers in Madrasah Tsanawiyah have great potential but are often hindered by a lack of participation in decision-making. This study employs a qualitative approach with a case study design, collecting data through in- interviews, observation, and documentation. The research findings indicate that a collaborative approach involving active involvement between the principal and teachers in planning and evaluating learning, as well as classroom supervision that ensures the effectiveness of the learning process, instructional supervision that focuses on improving the quality of teaching, constructive feedback that builds, and continuous evaluation to ensure teacher professional development. This study suggests that the shift from a top-down supervision model to a participatory supervision model can enhance teacher performance in Madrasah Tsanawiyah. This collaborative approach is expected to strengthen the role of teachers in decision-making, improve the quality of learning, and support the continuous development of teacher professionalism.